DEVELOPMENT OF CREATIVE ACTIVITY OF PRIMARY CLASS STUDENTS (Conferencea, 2024)
This article talks about the development of creative activity of primary school students. Based on scientific data, the author studied and analyzed the specific aspects of the development of creative activity of elementary school students based on existing literature.